2019
DOI: 10.4081/jphr.2019.1436
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy: An Overview on Parents' Opinions about Vaccination and Possible Reasons of Vaccine Refusal

Abstract: Background. Vaccine hesitancy has increased worldwide with a subsequent decreasing of vaccination rates and outbreaks of vaccine-preventable diseases (i.e. measles, poliomyelitis and pertussis) in several developed countries, including Italy. Design and Methods. We conducted a survey to investigate the attitudes of a parents’ sample about vaccinations by the distribution of questionnaires in six lower secondary schools of the Italian city of Messina. Results. Regarding vaccinations carried out on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 35 publications
5
101
3
6
Order By: Relevance
“…Previous bad experience with pentavalent vaccine has been highlighted as the most common reason for hesitancy or refusal, which is supported by other studies in the past. 22,23 Similarly, vaccine hesitancy related to other vaccines such as pertussis, measles, mumps, and rubella (MMR) has been reported in previous studies. 24,25 Elliott et al in his study from north India found that measles is the most commonly omitted vaccine in the primary course and first and second boosters of diphtheria, pertussis and tetanus toxoid are most commonly missed vaccines.…”
Section: Discussionmentioning
confidence: 71%
“…Previous bad experience with pentavalent vaccine has been highlighted as the most common reason for hesitancy or refusal, which is supported by other studies in the past. 22,23 Similarly, vaccine hesitancy related to other vaccines such as pertussis, measles, mumps, and rubella (MMR) has been reported in previous studies. 24,25 Elliott et al in his study from north India found that measles is the most commonly omitted vaccine in the primary course and first and second boosters of diphtheria, pertussis and tetanus toxoid are most commonly missed vaccines.…”
Section: Discussionmentioning
confidence: 71%
“…Bugüne kadar yapılan araştırmalar, aşı tereddüt nedenlerinin dünya genelinde yıllar içinde değiştiğini göstermiştir. 13,14 Aşılamaya karar verme sürecinin gelişimi Şekil 1'de görülmektedir.…”
Section: Aşi Kararsizliği Nedenleri̇ Ve Sonuçlariunclassified
“…Özellikle eğitim düzeyi düşük ailelerin, enfeksiyonlar konusunda bilgilerinin olmaması ve toplumsal sağlık bilinçlerinin düşük olmasının, çocukların aşılanması ve/veya zamanında aşılanması konusunda ters bir etkiye sahip olduğu bilinmektedir. 13 ŞEKİL 1: Aşılamaya karar verme süreci.…”
Section: Aşi Kararsizliği Nedenleri̇ Ve Sonuçlariunclassified
“…Many studies have documented high rates of parental hesitancy around human papillomavirus (HPV) vaccination, contributing to delay of vaccination or vaccine refusal [1,2,3]. Low coverage rates have prompted a great deal of research on the determinants of HPV vaccination, and the literature consistently highlights the powerful in uence of healthcare providers' recommendations on parental HPV decisions and uptake; those who receive a provider recommendation are more likely to vaccinate their children than those who do not [1,4].…”
Section: Introductionmentioning
confidence: 99%